Human Neutrophils Respond to Complement Activation and Inhibition in Microfluidic Devices - Muldur, Sinan; Vadysirisack, Douangsone D.; Ragunathan, Sharan; Tang, Yalan; Ricardo, Alonso; Sayegh, Camil Elie; Irimia, Daniel (Frontiers in Immunology, 2021)
Complement activation is key to anti-microbial defenses by directly acting on microbes and indirectly by triggering cellular immune responses. Complement activation may also contribute to the pathogenesis of numerous inflammatory and immunological diseases. Consequently, intense research focuses on developing therapeutics that block pathology-causing complement activation while preserving anti-microbial complement activities. However, the pace of research is slowed down significantly by the limitations of current tools for evaluating complement-targeting therapeutics. Moreover, the effects of potential therapeutic agents on innate immune cells, like neutrophils, are not fully understood. Here, we employ microfluidic assays and measure chemotaxis, phagocytosis, and swarming changes in human neutrophils ex vivo in response to various complement-targeting agents. We show that whereas complement factor 5 (C5) cleavage inhibitor eculizumab blocks all neutrophil anti-microbial functions, newer compounds like the C5 cleavage inhibitor RA101295 and C5a receptor antagonist avacopan inhibit chemotaxis and swarming while preserving neutrophil phagocytosis. These results highlight the utility of microfluidic neutrophil assays in evaluating potential complement-targeting therapeutics.